“Perceptual Scotomas” - New, Joshua J.; Scholl, Brian J. (Psychological Science, 2008)
In motion-induced blindness (MIB), salient objects in full view can repeatedly fluctuate into and out of conscious awareness when superimposed onto certain global moving patterns. Here we suggest a new account of this striking phenomenon: Rather than being a failure of visual processing, MIB may be a functional product of the visual system's attempt to separate distal stimuli from artifacts of damage to the visual system itself. When a small object is invariant despite changes that are occurring to a global region of the surrounding visual field, the visual system may discount that stimulus as akin to a scotoma, and may thus expunge it from awareness. We describe three experiments demonstrating new phenomena predicted by this account and discuss how it can also explain several previous results.